Radio frequency rectification circuit with wide load range - LONG HAOXUAN; LIU JIAN (2024)
The invention provides a radio frequency rectifying circuit with a wide load range, which comprises an upper-layer microstrip structure, a middle dielectric substrate and a bottom-layer metal floor, and is characterized in that the upper-layer microstrip structure is printed on the upper surface of the middle dielectric substrate, and the bottom-layer metal floor is printed on the lower surface of the middle dielectric substrate; the upper-layer microstrip structure comprises an input end, a first high-voltage gain impedance conversion network, a second high-voltage gain impedance conversion network and a rectification network. According to the high-efficiency rectification circuit with the wide load range, relatively high rectification efficiency can be realized in a wide output load range; according to the invention, the working frequency f is equal to 900 MHz, and when the efficiency is greater than 50%, the output load range RL is equal to 2.0-43.5 k omega; the high-voltage gain impedance conversion netwo